The effect of experience quality on behavioral intentions of domestic tourists in visiting water parks - Davood Ghorbanzade; Hormoz Mehrani; Atena Rahehagh (Cogent Business & Management, 2019)
This study proposed a model to assess visitor experience quality and its effect on their image, perceived value, delight, satisfaction, and behavioral intentions in Iranian water parks. Based on convenience sampling, a sample of 384 visitors at five water parks in Mashhad, Iran was selected. Data were subjected to partial least squares analysis based on structural equation modeling (PLS-SEM). The findings of this study showed that quality of visitors' experiences significantly affects water park image, perceived value, and visitor's satisfaction. Also, water park image significantly affects perceived value, delight, and visitor's satisfaction. Moreover, perceived value and water park image exert a direct influence on customer satisfaction, and they also positively affect behavioral intentions. But, the visitor's delight affects indirectly and through satisfaction on behavioral intentions. Therefore, the results of this study will assist water parks management to develop and implement market-orientated service strategies both to increase experience quality and water park image and to enhance perceived value, delight, and satisfaction among visitors. It is hoped such changes will increase visitors' favorable behavioral intentions such as revisit and positive word of mouth from the water park in the future.
Keywords: 650; experience quality; perceived value; visitor delight; visitor satisfaction; behavioral intentions; water parks; Iran